Budaya Konsumtif Mahasiswa dalam Mengikuti Tren: Analisis Perspektif Karl Max - Retno Pangesti; Syarlla Zenia Aliah; Nazela Nazela; Vieronica Varbi Sununianti4; Istiqomah Istiqomah; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the consumptive culture of students in following trends using Karl Marx’s social class theory perspective. The phenomenon of consumptive behavior among students is no longer based on rational needs but is influenced by social, economic, and digital technological developments. This research uses a qualitative approach with a library research method by collecting and analyzing various relevant literature sources. The findings indicate that students’ consumptive behavior is part of modern capitalism mechanisms that shape consumption patterns through class relations, digital media, and social identity construction. From Marx’s perspective, consumption functions as a tool for reproducing the capitalist system that maintains social inequality, while Herbert Marcuse’s perspective reinforces that modern consumption is driven by “false needs” constructed through media and industry. In addition, factors such as family socioeconomic status, social environment, digital media, and the need for social recognition also strengthen students’ consumptive behavior. Therefore, student consumptive culture can be understood as a multidimensional phenomenon resulting from the interaction between economic, social, and ideological structures in modern society.